Jatropha curcas leaves mulch effect on seedling emergence and growth of maize (zea mays) - Irshad, Muhammad; Ullah, Faizan; Mehmood, Sultan; Khan, Asif Ullah (Penerbit Universiti Kebangsaan Malaysia, 2016)
Allelopathy is a process in which one plant species may usefully or adversely affect the growth of other plant species through the production of allelochemicals. During the present investigation, mulch effect of Jatropha curcas leaves was evaluated on seed germination and seedling growth of maize varieties viz. Pioneer (V1), Azam (V2) and Jalal (V3). Mulch was applied at 1 and 2 tons/hectare. Phenolic compounds were detected in Jatropha curcas leaf (131.15 mg gallic acid eq./gm extract). Mulch applied at 2 tons/hectare significantly reduced seed germination (%), germination index, relative water content, root width and seedling dry weight. From the findings of the present investigation, it was inferred that Jatropha curcas leaves exhibited phytotoxic effects on maize at high concentrations.